Fungal Stress Database (FSD)––a repository of fungal stress physiological data. (12th February 2018) - Orosz, Erzsébet; van de Wiele, Nathalie; Emri, Tamás; Zhou, Miaomiao; Robert, Vincent; de Vries, Ronald P; Pócsi, István
Abstract: The construction of the Fungal Stress Database (FSD) was initiated and fueled by two major goals. At first, some outstandingly important groups of filamentous fungi including the aspergilli possess remarkable capabilities to adapt to a wide spectrum of environmental stress conditions but the underlying mechanisms of this stress tolerance have remained yet to be elucidated. Furthermore, the lack of any satisfactory interlaboratory standardization of stress assays, e.g . the widely used stress agar plate experiments, often hinders the direct comparison and discussion of stress physiological data gained for various fungal species by different research groups. In order to overcome these difficulties and to promote multilevel, e.g. combined comparative physiology-based and comparative genomics-based, stress research in filamentous fungi, we constructed FSD, which currently stores 1412 photos taken on Aspergillus colonies grown under precisely defined stress conditions. This study involved altogether 18 Aspergillus strains representing 17 species with two different strains for Aspergillus niger and covered six different stress conditions. Stress treatments were selected considering the frequency of various stress tolerance studies published in the last decade in the aspergilli and included oxidative (H2 O2, menadione sodium bisulphite), high-osmolarity (NaCl, sorbitol), cell wall integrity (Congo Red) and heavy metal (CdCl2 ) stress exposures. In the future, we would like to expand this database to accommodate further fungal species and stress treatments. URL: http://www.fung-stress.org/